Antibiofillm activity of propolis extract on Fusarium species from onychomycosis - Galletti, Juliana (2017)
Aim: The present study evaluated the capacity of three species of Fusarium isolated from onychomycosis to form bio lms and the antibio lm effect of propolis extract on these bio lms. Materials & methods: The bio lms and antibio lm effects were evaluated by quantifying the colony-forming units, mitochondrial metabolic activity assays, total biomass by crystal violet staining and scanning electron microscopy. Results: Propolis extract demonstrated signi cant antibio lm ef ciency on Fusarium spp. isolates and reduced F. solani, F. oxysporum and F. subglutinans mature bio lms. Conclusion: Propolis extract can be an alternative topical treatment of onychomycosis caused by Fusarium spp.